2015
DOI: 10.1124/dmd.115.063206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Endoxifen and Other Major Metabolites of Tamoxifen on the Sulfation of Estradiol Catalyzed by Human Cytosolic Sulfotransferases hSULT1E1 and hSULT1A1*1

Abstract: Tamoxifen is successfully used for both treatment and prevention of estrogen-dependent breast cancer, yet side effects and development of resistance remain problematic. Endoxifen is a major active metabolite of tamoxifen that is being investigated for clinical use. We hypothesized that endoxifen and perhaps other major metabolites of tamoxifen may affect the ability of human estrogen sulfotransferase 1E1 (hSULT1E1) and human phenol sulfotransferase 1A1 isoform 1 (hSULT1A1*1) to catalyze the sulfation of estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recombinant human SULT1E1 (Squirewell and Duffel, 2015) and SULT2A1 (Gulcan et al, 2008) were expressed in Escherichia coli BL21 (DE3) cells, purified, and characterized as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant human SULT1E1 (Squirewell and Duffel, 2015) and SULT2A1 (Gulcan et al, 2008) were expressed in Escherichia coli BL21 (DE3) cells, purified, and characterized as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have argued that epithelial-mesenchymal transition, which is characterized by increased vimentin expression, might play a significant role in the development of E resistance [7]. In addition, Squirewell et al [14] argued that E may affect the ability of human Drug efflux transporters are involved in the decreased sensitivity of BC cells to TMX [9,10]. In the present study, the sensitivity of BC cells to E was diminished, which was followed by increased activities of the drug efflux transporters P-glycoprotein, BCRP, and MRP1.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may occur through the suppression of P-glycoprotein (MDR1) expression [16][17][18]. Squirewell et al [14] proposed a mechanism of the interactions of polyphenols, including CM, with ABC transporters and showed that polyphenols counteracted tumor cell chemoresistance by interacting with the ATP-binding domains of P-glycoprotein and inhibits its ATPase activity site and steroid interacting regions of the protein cytosolic domains [13]. However, for a flavonoid to interact with MRP1, it also needs transport stimulation of reduced glutathione [1,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human hSULT1E1 [315] and hSULT2A1 [316] were expressed in Escherichia coli BL21 (DE3) cells, purified, and characterized as described previously.…”
Section: Expression and Purification Of Hsult1e1 And Hsult2a1mentioning
confidence: 99%
“…Assays for the sulfation of estradiol catalyzed by SULT1E1 were conducted using a previously described method [317].…”
Section: Inhibition Of Hsult1e1 By Pcb Metabolitesmentioning
confidence: 99%